Revolutionizing Motorcycle Spare Part Sales at Bengkel Stel Velg Budyo with an Android-Based App: Revolusi Penjualan Spare Part Motor di Bengkel Stel Velg Budyo dengan Aplikasi Berbasis Android - Yodantius, Teddy; Taurusta, Cindy (Indonesian Journal of Innovation Studies, 2023)
The sales transactions of motorcycle spare parts in the service process are a very important part, especially in recording transaction data and available spare parts stock. Transactions at Bengkel Stel Velg Budyo are still manually recorded on paper. To improve the performance of Bengkel Stel Velg Budyo, a motorcycle spare parts sales application system is needed to help the workshop simplify sales transactions based on Android. The end result of the design and development of the motorcycle spare parts sales application is to design an application used to manage the transaction process as well as manage the stock of motorcycle spare parts at Bengkel Stel Velg Budyo so that transactions can be done effectively and efficiently. Highlights: 1. Manual recording of transactions on paper is a current issue at Bengkel Stel Velg Budyo 2. An Android-based application system is needed to improve the workshop's performance 3. The designed application aims to simplify sales transactions and manage motorcycle spare parts stock for effective and efficient transactions.